Identification of diving athletes’ sports specialization through their physical and functional attributes - Konopleva E.N.; Redi E.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the physical and functional attributes of athletes who excel in sailing, sprinting, and underwater sports. Methods and structure of the study. The research was conducted by a group of scuba divers, ranging in age from 18 to 25 years, consisting of 15 male and 15 female participants. Each participant is a member of the Krasnoyarsk Territory national team and holds a sports title of at least Master of Sports of Russia. The research employed a variety of methods, including the assessment of anthropometric and morphofunctional parameters, as well as the application of mathematical statistical techniques. Results and conclusions. Athletes who specialize in diving disciplines belong to the second type of morphofunctional physical development (MFTFR), according to the classification of O.N. Moskovchenko. These athletes have an athletic build and are typically of above-average height and light weight, which helps them to more easily overcome the surface of the aquatic environment. Scuba divers who specialize in sprinting and other underwater disciplines also belong to this group. Swimmers, on the other hand, have a longer body and higher weight, which allows them to perform speed and power work at a high level. Data obtained from the study can be used as an effective tool in training scuba divers, as it provides insight into the interrelation between sports specialization and morphofunctional characteristics. This information can serve as a scientific foundation for organizing the training process.. The dynamics of changes in morpho-functional parameters depending on specialization provide an opportunity to justify the choice of an underwater sport, which allows predicting a high performance of an athlete and personalizing the training process.